Placa aterosclerótica à angiotomografia de coronárias em pacientes com escore de cálcio zero - Gabriel, Fabíola Santos (2017)
Background: In view of the high mortality due to Cardiovascular Diseases in the world, a stratification of the main risk factors and correct choice of the diagnostic modality is necessary. Several studies have shown that the calcium score (CS) has a low risk of cardiovascular events. However, the frequency of individuals with coronary atherosclerotic plaques and zero CS is conflicting in the specialized medical literature. Objective: To evaluate the frequency of coronary atherosclerotic plaques and associated factors in patients with CS. Methods: This was a prospective, cross-sectional study with 367 volunteers with zero CS through the realization CS test and coronary computed tomography angiography (CCTA), from 2011 to 2016, in four imaging centers. The sample was obtained for convenience and consecutively. Results: The frequency of atherosclerotic plaque in the coronary arteries of the 367 patients with zero CS was 9.3% (34 individuals); in this subgroup the mean age was 52 ± 10 years, 18 (52.9%) were women and 16 (47%) had significant coronary obstructions (> 50%), some in more than one segment. The frequency of non-obese individuals (90.6% vs 9.4%, p = 0.037) and those of alcoholics (55.9% vs 44.1%, p = 0.015) was significantly higher in patients with atherosclerotic plaques, Variable, odds ratio of 3.4 for the development of these plaques. Conclusions: The frequency of atherosclerotic plaque with zero CS was considerable, evidencing that the absence of calcification, through the CCTA, does not exclude plaque and nor obstructive lesion, mainly in the non-obese and the alcoholic.